Faktor-Faktor Penentu Keputusan Pendanaan Perusahaan di Indonesia - Sumanti, Elvis; Mulik, Mexi (JBE (Journal of Business and Economics); Volume 10 No.2, 2011 JBE UNKLAB, 2011)
This research examines the impact of profitability and growth opportunity toward financing decision made by company. The sample of this study is manufacturing company listed on IDX for the period 2007-2010. Simple linear regression is used to test whether profitability and growth opportunity are capital structure determinants. The results of the study find that both profitability and growth opportunity positively significantly affect financing decision as reflected in company’s capital structure.